2014
DOI: 10.1097/igc.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Patients With Stage IIIC Endometrial Cancer

Abstract: The number of debulked metastatic lymph nodes and PA involvement were associated with recurrence in the univariate analysis. The presence of recurrence was the only independent prognostic factor detecting survival. Therefore, systematic lymphadenectomy involving PA lymph nodes instead of sampling should be performed in patients with high risk for nodal involvement in endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…LNM is one of the most important prognostic factors for EC; therefore, the prediction of LNM preoperatively has a critical significance in the treatment plan [12]. Preoperative CA125 level is useful as a reliable tumor marker in the management of EC [3,6,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…LNM is one of the most important prognostic factors for EC; therefore, the prediction of LNM preoperatively has a critical significance in the treatment plan [12]. Preoperative CA125 level is useful as a reliable tumor marker in the management of EC [3,6,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 77% of metastatic lymph nodes in the paraaortic region were located between the inferior mesenteric artery and the renal vein [16]. Turan et al [17] also reported similar rates of metastatic lymph node locations as 38% only pelvic, 45% pelvic and paraaortic, and 16% only paraaortic in their study. Odagiri et al [18] evaluated the recurrence pattern and survival of 147 patients with stage IIIC1 to IIIC2 endometrial carcinoma, and they concluded that recurrence is the only independent prognostic factor for survival and the number of harvested lymph nodes along with paraaortic lymph node metastasis predicted the recurrence risk.…”
Section: Discussionmentioning
confidence: 55%
“…Recurrence rate varying according to clinical factors, stage and pathologic findings; is approximately 11-13% within 2 years after initial treatment in EC patients (3)(4)(5). Extra-pelvic disease was present in 70% of recurrent patients' diagnosed high grade EC (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%